2013
DOI: 10.1016/j.adolescence.2013.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the joint effects of family and other developmental contexts on the sense of coherence (SOC): A person‐focused analysis using the Classification Tree

Abstract: Using a person‐focused approach, the present study sought to identify meaningful constellations of contextual factors that led to predominantly high and low levels of sense of coherence (SOC). Specifically, the contributions of the quality of parent–child relationships, teacher and classmate support, models of behaviour in the peer group, and neighbourhood assets were examined in a representative sample of Spanish adolescents aged 13 to 18 that had taken part in the 2010 edition of the study Health Behaviour i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 99 publications
(101 reference statements)
1
30
0
1
Order By: Relevance
“…Several studies have focused on quantitatively assessing the correlations between SOC and various health behaviours (Humphrey & McDowell, 2013) and health outcomes such as emotional health (Moksnes, Espnes, & Lillefjell, 2012) and mental health (Lekkou, Åström, & Hägglöf, 2007). In addition, researchers have begun to study how SOC develops in childhood and early adulthood (García-Moya, Moreno, & Jiménez-Iglesias, 2013;Marsh, Clinkinbeard, Thomas, & Evans, 2007). However, further research is necessary to examine the factors that contribute to the development of SOC, the role of various developmental contexts in building up SOC (García-Moya et al, 2013) and the possibilities for strengthening SOC explicitly, for example in sport-for-development settings (Super, Wagemakers, Picavet, Verkooijen, & Koelen, 2015).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have focused on quantitatively assessing the correlations between SOC and various health behaviours (Humphrey & McDowell, 2013) and health outcomes such as emotional health (Moksnes, Espnes, & Lillefjell, 2012) and mental health (Lekkou, Åström, & Hägglöf, 2007). In addition, researchers have begun to study how SOC develops in childhood and early adulthood (García-Moya, Moreno, & Jiménez-Iglesias, 2013;Marsh, Clinkinbeard, Thomas, & Evans, 2007). However, further research is necessary to examine the factors that contribute to the development of SOC, the role of various developmental contexts in building up SOC (García-Moya et al, 2013) and the possibilities for strengthening SOC explicitly, for example in sport-for-development settings (Super, Wagemakers, Picavet, Verkooijen, & Koelen, 2015).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In addition, researchers have begun to study how SOC develops in childhood and early adulthood (García-Moya, Moreno, & Jiménez-Iglesias, 2013;Marsh, Clinkinbeard, Thomas, & Evans, 2007). However, further research is necessary to examine the factors that contribute to the development of SOC, the role of various developmental contexts in building up SOC (García-Moya et al, 2013) and the possibilities for strengthening SOC explicitly, for example in sport-for-development settings (Super, Wagemakers, Picavet, Verkooijen, & Koelen, 2015). As sport is often seen as a promising setting for positive youth development, taking a salutogenic approach we aim to complement the current literature in the field by investigating how community sports coaches create optimal social conditions for life skill development and transferability.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Relationships with parents (Feldt et al, 2005;García-Moya et al, 2012), support from teachers and classmates (García-Moya et al, 2013d;Natvig et al, 2006), behavioural models in the peer group (García-Moya et al, 2013b) and neighbourhood quality (García-Moya et al, 2013a;Marsh et al,2007) have all been identified as potential precursors of SOC during adolescence.…”
Section: Salutogenesis and Explanationmentioning
confidence: 99%
“…Interest in the idea also re-emerged in the 21 st century in the context of public health and its efforts to reduce health inequalities (Morgan and Ziglio, 2007;Eriksson and Lindström, 2008). Most notably, the work of Lindstrom and and others (García-Moya et al, 2013b;Mittelmark and Bull, 2013) have highlighted its theoretical potential both in academic and practice circles and have gone some way to enhance the evidence base to demonstrate its worth as a health concept. Pivotal works include the seminal systematic reviews on the links of sense of coherence (SOC -the central construct of salutogenesis) with wellbeing and quality of life Lindström, 2006, 2007), and a systematic review about SOC in adolescent samples (Rivera et al, 2013) -see methods section for further details.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation